Physiological and sport-specific skill response of Olympic youth soccer athletes - Vanderford, M. L.; Meyers, M. C.; Skelly, W. A.; Stewart, C. C.; Hamilton, K. L. (The Journal of Strength and Conditioning Research, 2004)
Although many studies have been focused on soccer athletes, no comprehensive studies have been conducted on adolescent soccer athletes in the United States. Therefore, the purpose of this study was to quantify the physiological and sport-specific skill characteristics of Olympic Developmental Program (ODP) soccer athletes by age group and game experience. Following written, informed consent, 59 male athletes (age = 14.6 ± 2.0 years; wt = 60.5 ± 1.4 kg; ht = 172.4 ± 1.2 cm) completed a battery of tests to determine aerobic power (O2max), heart rate (HRmax), ventilation (VEmax), respiratory exchange ratio (RER), anaerobic threshold (AT), blood pressure (BPrest/max), anaerobic power/capacity [peak power (PP), mean power (MP), total work output (TWO), fatigue index (FI)], leg power [vertical squat jump (VJS), countermovement jump (VJC)], body composition [percent body fat (%BF), lean body mass (LBM)], joint range of motion (trunk, back, hip, knee, and ankle), and agility/sport-specific skills (T-test, line drill test, juggling test, Johnson wall volley, and modified-Zelenka circuit). Factor analyses with subsequent multivariate analyses of variance (MANOVAs) indicated significant main effects across age (p = 0.0001) but not by game experience (p = 0.82). Older athletes exhibited greater height, weight, LBM, VEmax, Timemax, PP, TWO, and VSJ values than younger athletes. Although not significant, there were differences with increasing age in the agility tests (T-test, wall volley, and juggling test). In conclusion, improvements in anaerobic power, agility, and sport-specific skill should be addressed at this developmental level of competition.